English Figurative Language on Palembang Hotel Websites - Wijaya, Beni; Zakaria; Yeny, Eli; Fadhil, Mohamad (Institut Agama Islam Negeri Palopo, 2025)
Websites for hotels are essential sources of information for prospective guests. Because of this, their readability and appeal are crucial to hotel internet marketing. The objective of this study is to gain insight into the linguistic strategies utilized by hotels for online promotion. This study initially introduces an analytical framework grounded in appraisal theory to elucidate the underlying mechanisms employed by hotels to foster interpersonal interactions. This framework is subsequently employed to analyze the online linguistic strategies utilized by the five-star hotels in Palembang. The overall linguistic strategy is found, along with the hotels' preference for using it. This study employed a descriptive qualitative methodology, analyzing samples from hotel websites in Palembang based on their usage of language style. The findings indicated that metonym, hyperbole, metaphor, personification, simile, and synecdoche are the language types that the hotel frequently uses to entice readers to stay there with metaphor as the most dominant. In conclusion, one of the most important parts of making ads is using language style, which means changing the meaning of words and using figurative language to make them more fun to read.